2012
DOI: 10.1007/s10725-012-9748-5
|View full text |Cite
|
Sign up to set email alerts
|

Administration of isothiocyanates enhances heat tolerance in Arabidopsis thaliana

Abstract: Although it has been documented that plants generate isothiocyanates (ITCs) through the glucosinolate-myrosinase system to defend against biotic stresses, the roles of ITCs in defending against abiotic stresses have scarcely been studied. Here, we report that exogenously applied ITCs enhance the heat tolerance of Arabidopsis thaliana. Pre-administration of phenethyl ITC to Arabidopsis plants mitigated growth inhibition after heat stress at 55 o C for 1 h. Although methyl ITC and allyl ITC also tended to reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 25 publications
1
44
0
1
Order By: Relevance
“…This phenomenon indicated that some adverse impacts from endogenous JA deficiency may be alleviated by exogenous MeJA application. In addition to antibacterial activity and insect resistance, isothiocyanates also act as heat tolerance enhancers in plant45. Khokon et al .…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon indicated that some adverse impacts from endogenous JA deficiency may be alleviated by exogenous MeJA application. In addition to antibacterial activity and insect resistance, isothiocyanates also act as heat tolerance enhancers in plant45. Khokon et al .…”
Section: Resultsmentioning
confidence: 99%
“…Among the volatile forms methyl salicylate [128] and methyl benzoate have an important activity in plant defense from pathogens [129]. Another well-known benzenoid is salicylic acid (SA), a plant hormone that has been traditionally involved in pathogen defense [130] but has been proved effective in alleviating the damage induced by several abiotic stress conditions [131]. Mechanistically, SA may induce little bursts of H 2 O 2 production resulting in mild oxidative stress which, in turn, could enhance the antioxidant activity, improving stress tolerance [132].…”
Section: Effect Of Abiotic Stress On Plant Biochemistry: Metabolitmentioning
confidence: 99%
“…LudwigMüller et al (2000) also observed that the TU8 mutant of Arabidopsis, which has a lack in glucosinolate metabolism, was significantly more affected by high temperature than wild-type plants. Moreover, the exogenous application of phenethyl isothiocyanate to A. thaliana plants enhanced heat tolerance, increasing the expression levels of HSP70 (heat shock protein) genes, therefore this isothiocyanate could be involved in the resistance against high temperature stress (Hara et al 2013). …”
Section: Defense Against Abiotic Stressmentioning
confidence: 99%